Elaboración de una guía práctica para el uso eficiente de la energía en empresas MiPYMES del Sector Alimenticio en Costa Rica - Zúñiga-Araya, Melanny (Instituto Tecnológico de Costa Rica, 2014)
Costa Rica is making a great effort to strengthen the corporate MSMEs. However, it has neglected the efficient use of energy in them. This pilot research examines this issue on seven micro food companies (bakeries, catering service, jam making) which are located in the GAM. This research involved field visits and energy audits whose purpose was to determine the current business situation and to design and implement a Guide for Efficient Use of Energy, sought to involve the MSMEs in the efficient use of energy and the outsourcing the actual cost of the energy in the cost of the products. Besides energy indices were calculated and showed improvement opportunities in the enterprises as well as the evaluation of one of the companies ECOs. Energy consumption of the companies which were analyzed; 69% is used in refrigeration and requires an annual expenditure of ₡ 3 745 278. Similarly, the environmental impact of energy consumption was measured by means of equivalent tons of CO2 (19, 45 ton CO2 equivalents per year) identifying the company emits more GHG is using wood as the main fuel. Moreover the research showed the lack of knowledge in basic and technical aspects of consumption and energy use in participating companies; emphasizing the importance of studies attempting to improve in this aspect.
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Química, 2014.
Keywords: Recursos energéticos; Pequeñas y medianas empresas; Auditoría energética; Índices; Combustibles